A rapid review of the benefits and challenges of dynamic consent - Winnie Lay; Loretta Gasparini; William Siero; Elizabeth K Hughes (Research Ethics Review)
Dynamic consent is increasingly recommended for longitudinal and biobanking research; however, the value of investing in such systems is unclear. We undertook a rapid review of the benefits and challenges of implementing dynamic consent by searching five databases (Ovid Medline, Ovid Embase, Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature – CINAHL) for articles published up to May 2023 that report on participants’ or researchers’ experience of dynamic consent. From 1611 papers screened, 12 met inclusion criteria. Guided by thematic analysis with an inductive approach, we synthesised 31 benefits and 8 challenges. Benefits included: enhanced participant experience through improved consent management and tailoring; greater participant engagement and retention through increased autonomy, trust and communication; reduced costs and burden and increased accessibility and inclusivity. Participants and researchers also valued additional features that dynamic consent platforms facilitate such as two-way communication and return of research updates. The main challenges included the digital divide and consent fatigue. The papers gave recommendations to mitigate these challenges, for example by supplementing with other communication tools and allowing a broad consent approach, respectively. Overall, dynamic consent was described as a valuable consent approach with many benefits and some surmountable challenges. Most included literature was qualitative, so further research is needed to quantify the impact of dynamic consent on recruitment, retention, and participant experience. Further long-term investigations are necessary to explore whether participants want to and do change their consent over time, as well as the impact of dynamic consent on participant privacy.